The 14‐3‐3 protein YWHAB inhibits glucagon‐induced hepatic gluconeogenesis through interacting with the glucagon receptor and FOXO1. Issue 9 (21st March 2021) - Ji, Linlin; Wang, Qianqian; Liu, Mengdan; Zhu, Chaoyu; Xiao, Yuanyuan; Han, Junfeng; Fang, Yunyun; Ye, Jianping; Yin, Jun; Wei, Li
Abstract : Glucagon antagonism has been reported as a new therapeutic approach to hyperglycaemia. As the 14‐3‐3 protein YWHAB has been identified as a regulator of the glucagon receptor (GCGR) by affinity purification and mass spectrometry, we examined the role of YWHAB in vivo . Ywhab knockout mice display impaired blood glucose homeostasis only under pyruvate stimulation. Deletion of Ywhab in mouse primary hepatocytes (MPHs) increases hepatocyte glucose production by magnifying the effect of glucagon. Mechanistic analysis indicates that YWHAB forms a phosphorylation‐dependent complex with GCGR and directly interacts with forkhead box O1 (FOXO1). Together, these results reveal the inhibitory role of YWHAB in glucagon‐mediated hepatic glucose production, which may be a potential target for the control of gluconeogenesis and associated metabolic diseases. Abstract :